(untitled) (Intent Research Scientific Journal, 2023)
Writing is an extremely complex cognitive activity, in which the writer is required to demonstrate control over the variables at the same time. Well-written letters, reports and statements can improve students’ chances of success. Writing is an important factor in language. Some tips and strategies are provided to enhance learners’ writing skills.